Hungarian Monitoring, 15 July 1990 . [Magyar rádiófigyelő], 1990. július 15 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev-Kohl talks - Massive anti-Communist demonstration in Moscow - Latest arrests in Romania Domestic Affairs: - Árpád Göncz on his Czechoslovak visit - No visa requirements for France or Norway - Alleged takeover of power by Independent Smallholders', Agrarian Workers and Civic Party (FKGP) Economy: - Drastic price increases Külpolitika: - Gorbacsov-Kohl tárgyalások - Hatalmas antikommunista tüntetés Moszkvában - Újabb letartóztatások Romániában Belpolitika: - Göncz Árpád a csehszlovákiai látogatásáról - Vízummentesség Franciaországba és Norvégiába - A kisgazdapárt állítólagos hatalomátvétele Gazdaság: - Drasztikus áremelkedések